Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1992
DOI: 10.1002/bjs.1800790711
|View full text |Cite
|
Sign up to set email alerts
|

Use of Teflon stents for lymphovenous anastomosis

Abstract: The treatment of lymphoedema is difficult; conservative and surgical management show variable results. Lymphovenous anastomoses (LVAs) in experimental animals and patients give poor results in the treatment of primary lymphoedema and variable results in that of secondary lymphoedema. Conventional sutured LVAs were compared with anastomoses using polytetrafluoroethylene (Teflon) stents; 32 sutured and 21 stented LVAs were constructed in 16 rabbits with normal lymphatics. Anastomoses were assessed for quality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Our procedures for LVSEA have changed since May 2006, because ICG florescence lymphography and the stent method, 12 by which anastomoses can be performed more precisely, were introduced to our department at that time. The present study assessed midterm postoperative patency in LVSEA using ICG fluorescence lymphography in patients with peripheral lymphedema.…”
mentioning
confidence: 99%
“…Our procedures for LVSEA have changed since May 2006, because ICG florescence lymphography and the stent method, 12 by which anastomoses can be performed more precisely, were introduced to our department at that time. The present study assessed midterm postoperative patency in LVSEA using ICG fluorescence lymphography in patients with peripheral lymphedema.…”
mentioning
confidence: 99%
“…In animal models, Tourani et al reported obstruction of nearly 50% of LVAs at just 5 months postoperatively, 33 identifying lymphatic thrombosis because of retrograde venous flow as the likely reason for failure. [34][35][36][37] When comparing our LYMPHA technique to other published series, there is little variation, including the number of lymphatics anastomosed per patient. 20,23 Despite these similarities, it is still possible that subtle operative maneuvers may have a larger effect on long-term patency of LVAs.…”
Section: Discussionmentioning
confidence: 98%
“…2 Innovation techniques that have been reported to overcome these constraints can be divided into two categories: innovations in anastomotic technique and innovations in anastomotic configuration. [2][3][4][5][6][7][8][9] In early-stage lymphedema, the lymphatic vessels are not dilated, and it is challenging to secure the lymphatic lumen. In our report, the average outer diameter of lymphatic vessels anastomosed using the modified PIST was 0.36 mm (0.2-0.6 mm).…”
Section: Discussionmentioning
confidence: 99%
“…2 Innovation techniques that have been reported to overcome these constraints can be divided into two categories: innovations in anastomotic technique and innovations in anastomotic configuration. 2–9…”
Section: Discussionmentioning
confidence: 99%